Analysis of skin conductance response during evaluation of preferences for cosmetic products - Ohira, Hideki; Hirao, Naoyasu (Frontiers in Psychology, 2015)
We analyzed skin conductance response (SCR) as a psychophysiological index to evaluate affective aspects of consumer preferences for cosmetic products. To examine the test-retest reliability of association between preferences and SCR, we asked 33 female volunteers to complete two experimental sessions approximately 1 year apart. The participants indicated their preferences in a typical paired comparison task by choosing the better option from a combination of two products among four products. We measured anticipatory SCR prior to expressions of the preferences. We found that the mean amplitude of the SCR elicited by the preferred products was significantly larger than that elicited by the non-preferred products. The participants’ preferences and corresponding SCR patterns were well preserved at the second session 1 year later. Our results supported cumulating findings that SCR is a useful index of consumer preferences that has future potential, both in laboratory and marketing settings.